Renal Effects of Anchomanes difformis Crude Extract in Wistar Rats - Jacob Ataman E; MacDonald Idu (Mashhad University of Medical Sciences, 2014)
Objective:  Anchomanes difformis is a member of the plant family Araceae which is used as a diuretic but also has other medicinal applications. This study investigates the dietary effects of A. difformis on the kidneys of adult wistar rats. Materials and Methods: Sixteen rats were used and were weighed, before and after the experiment. All rats were randomly divided into four groups. All groups were treated with the following regimen for two weeks. The control group (A) was fed on feed mash and water ad libitum throughout the period. The treatment groups B, C, and D received feed mash mixed with crude extract of A. difformis in the following proportions: 25:75(g), 50:50(g), and 75:25(g), respectively. The kidneys of the experimental animals were histologically examined for morphologic changes. Results: Results showed a significant difference (p